Pengaruh Inklusi Karet dan Semen yang Mengandung Graphene Oxide terhadap Perilaku Sifat Fisis dan Mekanis Tanah - Faruqi, Muhammad Alfian; Mohammed, Bashar S; Anwar, Abdullah; Dharmawansyah, Dedy; Hermansyah, Hermansyah (Department of Civil Engineering, Diponegoro University, 2023)
Improving the physical properties of problematic soil has became fundamental consideration in various constructions, especially geotechnical engineering, to avoid failures, increase stability and strength of soil. Silty sand is one of the problematic soils and often encountered in the field where the fine gradation contained in the soil allows the soil to easily deform under pressure and lateral forces. In this study, silty sand was mixed with three variations of crumb rubber content (5, 10, and 15% based on soil weight), 6% cement (based on soil weight), and 0.05% graphene oxide (based on cement weight) to measurement and analysis of physical and mechanical properties. Soil Consistency limits, compaction testing using the Proctor Apparatus, and direct shear test were carried out for each mixed variable. The test results showed that the consistency limits and dry density decreases with increasing rubber content in the soil-cement matrix containing graphene oxide. Substitution of graphene oxide into the soil-cement matrix was able to increase in the stress and shear strength of the soil at each in variation in rubber content.